Multisite musculoskeletal pain in migrants from the Indian subcontinent to the UK: a cross-sectional survey - Rizzello, E. (BMC Musculoskelet Disord, 2019)
BACKGROUND: Recent findings indicate that wide international variation in the prevalence of disabling regional musculoskeletal pain among working populations is driven by unidentified factors predisposing to pain at multiple anatomical sites. As a step towards identification of those factors, it would be helpful to know whether the prevalence of multisite pain changes when people migrate between countries with differing rates of symptoms; and if so, whether the change is apparent in first generation migrants, and by what age it becomes manifest. METHODS: To address these questions, we analysed data from an earlier interview-based cross-sectional survey, which assessed the prevalence of musculoskeletal pain and risk factors in six groups of workers distinguished by the nature of their work (non-manual or manual) and their country of residence and ethnicity (UK white, UK of Indian subcontinental origin and Indian in India). Prevalence odds ratios (ORs) with 95% confidence intervals (CIs) were estimated by logistic regression. RESULTS: Among 814 participants (response rate 95.4%), 20.6% reported pain at ≥3 anatomical sites. This outcome was much less frequent in Indian manual workers than among white non-manual workers in the UK (adjusted OR 0.06, 95%CI 0.01–0.36), while rates in Indian non-manual workers were intermediate (OR 0.29, 95%CI 0.12–0.72). However, within the UK, there were only small differences between white non-manual workers and the other occupational groups, including those of Indian sub-continental origin. This applied even when analysis was restricted to participants aged 17 to 34 years, and when second and later generation migrants were excluded. CONCLUSIONS: The observed differences in the prevalence of multisite pain seem too large to be explained by healthy worker selection or errors in recall, and there was no indication of bias from differences in understanding of the term, pain. Our findings suggest that whatever drives the higher prevalence of musculoskeletal pain in the UK than India is environmental rather than genetic, affects multiple anatomical sites, begins to act by fairly early in adult life, and has impact soon after people move from India to the UK. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12891-019-2494-3) contains supplementary material, which is available to authorized users.